Pengaturan Transplantasi Organ yang Berkeadilan : Upaya Pencegahan Komersialisasi Organ Tubuh Manusia - Evanadya Izza Nurrahmah; Yovita Arie Mangesti (JUSTNESS - Jurnal Hukun Politik dan Agama, 2025)
Law Number 17 of 2023 on Health explicitly prohibits all forms of organ trade and commercialization, regardless of the reason. This provision is intended to prevent organ trafficking practices that violate human dignity and ethical principles in healthcare. However, the law does not clearly define the scope or meaning of “organ trade” and “commercialization,” which creates challenges in terms of legal certainty. A particular dilemma arises when a recipient voluntarily gives money to a donor as a token of gratitude, without any prior agreement or transactional intent. This study adopts a normative legal method by analyzing Law Number 17 of 2023 and related regulations. The findings show that current legal provisions do not offer detailed parameters to distinguish between illegal organ trade and voluntary, humanitarian-based expressions of appreciation. As a result, there is an urgent need for supplementary regulations or more detailed implementing provisions to ensure legal clarity, prevent the criminalization of good-faith donors, and provide adequate legal protection for all parties involved in voluntary, non-commercial organ donation.